1995
DOI: 10.1007/bf00156415
|View full text |Cite
|
Sign up to set email alerts
|

Foveal avascular zone in macular branch retinal vein occlusion

Abstract: The mean area of the foveal avascular zone (FAZ) in normal subjects was reported as 0.231 mm2 to 0.405 mm2, using fluorescein angiography. The FAZ enlarges in vaso-occlusive diseases, especially diabetic retinopathy, sickle cell retinopathy, talc retinopathy and branch retinal vein occlusion. In the present study the FAZ of 20 patients affected by macular branch retinal vein occlusion (MBRVO) was compared with the FAZ of 41 control subjects. The FAZ mean area was 0.56 +/- 0.34 mm2 SD in the MBRVO group, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 21 publications
1
66
0
3
Order By: Relevance
“…In non-diabetic subjects, the size of the FAZ has been reported to be between 0.2 and 0.4 mm 2 [6,10,[25][26][27]. In diabetic patients with retinopathy, the FAZ is enlarged [26], particularly in patients with reduced visual acuity [28].…”
Section: Discussionmentioning
confidence: 99%
“…In non-diabetic subjects, the size of the FAZ has been reported to be between 0.2 and 0.4 mm 2 [6,10,[25][26][27]. In diabetic patients with retinopathy, the FAZ is enlarged [26], particularly in patients with reduced visual acuity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous publications that documented it, 8,10,21 we classified the macula as either perfused with a capillary plexus around the entire circumference of the FAZ or non-perfused, in which the FAZ was in contact with the NPA.…”
Section: Fluorescein Angiographymentioning
confidence: 99%
“…Several studies have reported that an enlarged foveal avascular zone (FAZ) is correlated with the visual acuity (VA), and the disrupted macular microcirculation is involved in MO associated with BRVO. 9,10 In contrast, Finkelstein 8 reported a better prognosis in eyes with ischaemic macula associated with BRVO. Although it is evident that retinal ischaemia exacerbates dysfunction in the affected retina, the controversy suggests that pathology other than macular ischaemia, such as MO, causes visual dysfunction.…”
Section: Introductionmentioning
confidence: 97%
“…5 Previous studies have further shown an enlargement of the foveal avascular zone (FAZ) in patients with retinal vein occlusion. 6,7 Until recently, the only way to evaluate the FAZ was by fluorescein angiography (FA), an invasive and time consuming examination associated with adverse effects including nausea, vomiting, rash, and even anaphylaxis and sudden death. 8,9 Furthermore, during the early stages of CRVO, FA has several limitations in providing information about retinal capillary obliteration due to hemorrhage and edema.…”
mentioning
confidence: 99%